Interpretasi Konsep Accelerationism; Kapitalisme yang Berjalan dalam Film Interstellar (2014) dan The Platform (2019) - Syahadah, Amalia Utammi; Tambunan, Shuri Mariasih Gietty; Suharjo, Rias Antho Rahmi (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
Accelerationism plays a significant role in advancing scientific knowledge and the framework of human existence. Its contributions are manifested in facilitating convenient and swift access to information sources, digital communication, and the availability of diverse technological tools aiding various professions. On the contrary, accelerationism leads to a series of disparities between capitalism and modernism. It also results in humans losing control over themselves, time, and life and even contributes to destroying species and the environment. The situational analysis of accelerationism in this study aligned with Liu's findings in